المعالجة الإلكتروكيميائية للمياه الملوثة بالسالمونيلا - الصالح, فؤاد; كبيبو, عيسى; راعي, مجدي (Latakia University Journal -Basic Sciences Series, 2018)
This paper presents a novel safe technique for treating bacterial water. Electrochemical cell is a safe alternative rather than chlorine and hypochlorite on the disinfection of water. Several parameters such as, Current intensity, Anode mature were detected. Results show that under specific condition, Electrochemical could inactivate salmonella. That contamination of drinking water . يقدم هذا البحث تقنية آمنة وجديدة في تطهير المياه من الملوثات البكتيرية وأن الخلية الإلكتروكيميائية أكثر أمناً من استخدام الكلور والهيبوكلوريت في تطهير المياه. واستخدم العديد من البارامترات مثل كثافة التيار وطبيعة الأنود كانت النتيجة وتحت الشروط الخاصة أنه أدى إلى تثبيط السالمونيلا الملوثة لمياه الشرب.